2009
DOI: 10.1016/j.neunet.2009.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Bias, optimal linear estimation, and the differences between open-loop simulation and closed-loop performance of spiking-based brain–computer interface algorithms

Abstract: The activity of dozens of simultaneously recorded neurons can be used to control the movement of a robotic arm or a cursor on a computer screen. This motor neural prosthetic technology has spurred an increased interest in the algorithms by which motor intention can be inferred. The simplest of these algorithms is the population vector algorithm (PVA), where the activity of each cell is used to weight a vector pointing in that neuron’s preferred direction. Off-line, it is possible to show that more complicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
123
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(129 citation statements)
references
References 39 publications
4
123
0
Order By: Relevance
“…Experiments with BMI have also suggested that closed-loop control can partially compensate decoder bias, which is systematic error in the decoded velocity (Chase et al, 2009;Jarosiewicz et al, 2008;Koyama et al, 2010). To examine this possibility, we compared open-loop versus closed-loop behavior in the PVA (Georgopoulos et al, 1986), which is known to be a biased variation on the OLE (Chase et al, 2009).…”
Section: Decoder Bias In Open Versus Closed-loop Behaviormentioning
confidence: 99%
See 4 more Smart Citations
“…Experiments with BMI have also suggested that closed-loop control can partially compensate decoder bias, which is systematic error in the decoded velocity (Chase et al, 2009;Jarosiewicz et al, 2008;Koyama et al, 2010). To examine this possibility, we compared open-loop versus closed-loop behavior in the PVA (Georgopoulos et al, 1986), which is known to be a biased variation on the OLE (Chase et al, 2009).…”
Section: Decoder Bias In Open Versus Closed-loop Behaviormentioning
confidence: 99%
“…To examine this possibility, we compared open-loop versus closed-loop behavior in the PVA (Georgopoulos et al, 1986), which is known to be a biased variation on the OLE (Chase et al, 2009). Error in the decoded angle of movement was averaged over multiple trials for each of eight movement directions.…”
Section: Decoder Bias In Open Versus Closed-loop Behaviormentioning
confidence: 99%
See 3 more Smart Citations